Inspired by biology [ from molecules to materials to machines (National Academies Press, 2008)
resents a discussion of principles governing biomaterial design, a description of advanced materials for selected functions such as energy and national security, an assessment of biomolecular materials research tools, and an examination of infrastructure and resources for bridging biological and materials science